Editorial Note - David Warren (American Journal of Islam and Society)
This issue of the American Journal of Islam and Society (Volume 41 Nos. 3-4) comprises three main research articles, which respectively engage with the themes of political loyalty, justice and the just ruler, and popular preaching. We begin with Abdessamad Belhaj’s study, “Political Loyalty in Reformist Islamic Ethics: Resources and Limits.” We then turn to Fadi Zatari and Omar Fili’s contribution, “Justice and the Just Ruler in the Islamic Mirror of Princes.” For our third research article for this issue, we have Hatim Mahamid and Younis Abu Alhaija’s work, “Popular Religious Preaching as Informal Education and its Impact on Medieval Islamic Culture.”